Partial cystectomy with a bipolar sealing device in seven dogs with naturally occurring bladder tumors. Issue 4 (10th February 2020) - Milovancev, Milan; Scharf, Valery F.; Townsend, Katy L.; Singh, Ameet; Tremolada, Giovanni; Worley, Deanna; Schmiedt, Chad W.
Abstract: Objective: To describe the use of a bipolar sealing device (BSD) for partial cystectomy in dogs undergoing excision of bladder tumors. Study design: Multicenter, prospective, clinical pilot study. Sample population: Seven client‐owned dogs with nontrigonal urinary bladder lesions. Methods: Dogs underwent a sealed partial cystectomy with a BSD, with or without cystoscopic guidance of the resection. The sealed cystectomy site was oversewn with a single‐layer simple continuous pattern with monofilament absorbable suture. Results: Sealed partial cystectomy was successfully performed in all dogs, with a median surgical duration of 69 minutes (range, 50‐120). Lesions were located at the apex in six dogs and on the ventral midbody of the bladder in one dog. No urine leakage from the BSD luminal seal was visible prior to suture closure in three dogs, while varying amounts of urine leaked from the sealed site in four dogs. Suture was placed over the seal in grossly normal bladder tissue in six dogs and in the BSD peripheral thermal effect zone in one dog; in this latter dog, revision cystorrhaphy was required 3 days later because of uroabdomen. The other six dogs had no clinical evidence of urinary bladder healing complications. Conclusion: The integrity of the seal generated by the BSD tested here on partial cystectomies varied between dogs and was unpredictable. Clinical significance: Sealed partial cystectomy with a BSD may reduce exposure of urinary bladder luminal contents to the surgical site. However, the placement of sutures over the seal and through grossly normal bladder tissue is recommended to prevent postoperative uroabdomen.